Reflections on the thematic relevance of the evaluation of public policies (2018)
The paper analyses the issue of public policy evaluation based on the authors who have worked in this trans - disciplinary field in the social sciences. Therefore, it seeks to account for the evaluation of public policy as a relevant object in research. The corpus of the work studies the purposes, types and levels of public policy evaluation. Its application is presented through an example. In the end, the main research conclusion points to the complementary use of qualitative and quantitative methods for the sake of scientific rigor as a key to the dialogue of knowledge. Above all, it should be borne in mind that this article is reflective in nature.